Substantive green innovation or symbolic green innovation? The impact of ER on enterprise green innovation based on the dual moderating effects - Ganghui Lian; Aiting Xu; Yuhan Zhu (Journal of Innovation & Knowledge (JIK), 2022)
Based on the existing research on environmental regulation (ER) and enterprise innovation, this paper separates green innovation ability from general technological innovation and divides it, from the perspective of motivation, into substantive green innovation (SUBGI) and symbolic green innovation (SYMGI). This paper employs panel data of China's A-share listed enterprise from 2008 to 2018 in a difference-in-difference-in-difference model to construct a quasinatural experiment on the impacts of ER and the green innovation strategy of enterprises. Government subsidies and regulatory capture are used to explore the mechanism between ER and innovation behavior. The results show that ER has a significantly positive effect on green innovation, but its impact on SYMGI and SUBGI decreases. Under the constraints of the ER policy, government subsidies incentivize the green innovation of enterprises, but they are not the main reason for the difference between the two innovation behaviors. Regulatory capture plays a negative moderating role in ER promoting enterprises' SUBGI and has no significant impact on SYMGI, which is the key factor leading to the difference between the two innovation behaviors. The heterogeneity test suggests a pronounced promotion effect of ER on state-owned enterprises, large enterprises, and growing enterprises. This study provides momentous policy implications for making rational use of environmental policies in promoting enterprises' green innovation capability, especially high-quality green innovation behavior aimed at promoting enterprises' green technology progress and gaining competitive advantages.
Keywords: O31; O32; L1; L5; Q2; Q5; 650; Environmental regulation; Government subsidy; Difference-in-difference-in-difference model; Regulatory capture; Substantive green innovation; Symbolic green innovation